Are Nepali Customers Aware of Green Banking Practices?: Evidenced from Kapilvastu District of Nepal - Adhikari, Ujjwal; Gyawali, Santosh (Journal of Emerging Management Studies, 2024)
Purpose – To rid of the hazards of environmental degradation, it is imperative to integrate the efforts of governmental bodies along with well-designed policies, financial institutions implementing practical guidelines, and individuals promoting self-awareness. This paper aims to examine the status and impact of e-banking, green investment, and sustainable banking awareness on green banking of customers living in Kapilbastu district of Nepal. Design/methodology/approach – A quantitative approach-based causal-comparative research design was used. The data were gathered from 405 customers of banks in the Kapilvastu district using a five-point Likert scale questionnaire and non-probability convenience sampling technique. The data were processed and analyzed with EFA and CFA. Findings and Conclusion - The result has a significant impact of e-banking, green investment, and sustainable banking on green banking awareness. Customers who possessed knowledge about e-banking, green investment, and sustainable banking were inclined to green banking awareness and practices. Implications – The research findings could help bank managers to educate and re-educate the customers while receiving the bank services. Further, this paper also supports government and policy makers to make a concrete policy to shape green banking and sustainable financing practices which ultimately puts the forces in reaching UN’s sustaibale development goals. Originality/value – It is becoming increasingly clear that adopting green banking practices is not a one-time event; rather it necessitates a steady effort on the part of customers to raise awareness. The paper offers suggestions for raising awareness of green finance, which eventually relates to SDGs 7 and 13 goal for clean and affordable energy and goal for climate action. The paper outlines the three areas of green banking awareness: encouraging the use of new technology, lowering environmental impact (carbon footprint), and channeling the funds to sustainable projects.